Metabolic modulation of transcription: The role of one-carbon metabolism. Issue 12 (15th December 2022) - Lin, Jung-Ming G.; Kourtis, Savvas; Ghose, Ritobrata; Pardo Lorente, Natalia; Kubicek, Stefan; Sdelci, Sara
Summary: While it is well known that expression levels of metabolic enzymes regulate the metabolic state of the cell, there is mounting evidence that the converse is also true, that metabolite levels themselves can modulate gene expression via epigenetic modifications and transcriptional regulation. Here we focus on the one-carbon metabolic pathway, which provides the essential building blocks of many classes of biomolecules, including purine nucleotides, thymidylate, serine, and methionine. We review the epigenetic roles of one-carbon metabolic enzymes and their associated metabolites and introduce an interactive computational resource that places enzyme essentiality in the context of metabolic pathway topology. Therefore, we briefly discuss examples of metabolic condensates and higher-order complexes of metabolic enzymes downstream of one-carbon metabolism. We speculate that they may be required to the formation of transcriptional condensates and gene expression control. Finally, we discuss new ways to exploit metabolic pathway compartmentalization to selectively target these enzymes in cancer. Graphical abstract: Abstract : Metabolic enzymes and metabolic pathways have been recently shown to have non-canonical cellular functions. Here, Lin et al. focus on the non-canonical functions of the folate pathway with a particular focus on epigenetic regulation and condensate biology and provide a novel online tool to investigate metabolic essentiality.